Perancangan Sistem Informasi Tracking Task Management Berbasis PHP dan MySQL pada PT. Cakrawala Telekomunikasi Indonesia - Febriani, Yola; Hadi, Abrar (Antivirus : Jurnal Ilmiah Teknik Informatika, 2025)
PT. Cakrawala Telekomunikasi Indonesia is a company engaged in telecommunications distributor. Task management in this company is still conducted manually through verbal communication, leading to task completion delays, lack of transparency, and difficulties in monitoring work progress. Therefore, this study aims to develop a Tracking Task Management Information System based on PHP and MySQL using the Waterfall method to improve task distribution efficiency and transparency in work monitoring. The system development follows several stages: requirement analysis, system design, implementation, testing, and maintenance. The developed system enables managers to assign tasks to employees digitally, thus speeding up communication and minimizing errors in task distribution. The implementation results indicate that this system enhances work efficiency, reduces communication errors, and facilitates real-time task monitoring. With this system, the company can significantly improve productivity and work effectiveness.